The Impact of Government Expenditure in the Agriculture Sector on the Inclusiveness of Western Indonesia's Economic Growth - Utari, Tasya Nadya; Hutagaol, M. Parulian; Purnamadewi, Yeti Lis (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Economic growth, income inequality, and poverty are longstanding issues that are interesting to study. Inclusive economic growth is a model of economic growth that is often heard and sought to be implemented by various countries around the world. The increase in the government budget for the agricultural sector is expected to finance various programs, especially those aimed at increasing food production itself. This study aims to determine the level of inclusiveness of economic growth in Indonesia and to understand the impact of government spending in the agricultural sector on economic growth. The research method used in this study is panel data, utilizing secondary data processed with E-Views. The results of this study indicate that the economic growth in each province in Western Indonesia has been inclusive. Aspects of government spending in the agricultural sector that positively affect the inclusiveness of economic growth include fertilizer subsidies, irrigation infrastructure, and rural road infrastructure.